2019
DOI: 10.3390/e21050517
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Networks in Natural Languages

Abstract: We present a study of natural language using the recurrence network method. In our approach, the repetition of patterns of characters is evaluated without considering the word structure in written texts from different natural languages. Our dataset comprises 85 ebookseBooks written in 17 different European languages. The similarity between patterns of length m is determined by the Hamming distance and a value r is considered to define a matching between two patterns, i.e., a repetition is defined if the Hammin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Many studies focused on the complexity of natural language have pointed out that language is the manifestation of different levels of complex organization [ 1 4 ], ranging from semantics [ 5 ] to syntax [ 6 , 7 ] or even emotional components [ 8 ]. Of particular interest are the applications of network science on language organization, where these levels of complexity may be explored by means of single [ 9 , 10 ] and multilayer graphs [ 11 , 12 ]. A number of studies have reported emergent organizational properties in language based on associations of semantics, orthographic similarities [ 13 ] and phonetics [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies focused on the complexity of natural language have pointed out that language is the manifestation of different levels of complex organization [ 1 4 ], ranging from semantics [ 5 ] to syntax [ 6 , 7 ] or even emotional components [ 8 ]. Of particular interest are the applications of network science on language organization, where these levels of complexity may be explored by means of single [ 9 , 10 ] and multilayer graphs [ 11 , 12 ]. A number of studies have reported emergent organizational properties in language based on associations of semantics, orthographic similarities [ 13 ] and phonetics [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some previous studies, the levels of complexity have been evaluated in terms of modeling based on complex single-layer networks or their extension to multilayer networks [19][20][21]. Of particular interest are findings about emergent organizational properties that encompass facets of language ranging from semantics to phonetics, including the written structure of language [22][23][24][25]. In many of these network-based approaches, it has been found that the behavior of the connectives -the number of neighbors of a given node-is often described by distributions that lie between power-law a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 and narrow exponential behavior, depending on the language and the association criterion.…”
Section: Introductionmentioning
confidence: 99%